THE (RE)INVENTION OF MATHEMATICS TEACHING IN DIGITAL CULTURE: PERSPECTIVES FOR TEACHER EDUCATION - dos Santos, André Gomes; Schimiguel, Juliano (Seven Editora, 2025)
This article, "The (Re)Invention of Mathematics Teaching in Digital Culture: Perspectives for Teacher Education," addresses the crisis of school Mathematics, which still uses traditional and mechanistic methodologies in a world dominated by Digital Culture. It proposes that Digital Culture should be the lens through which pedagogical practice is re-signified, shifting the focus from transmission to the production and application of mathematical knowledge. The new epistemology of mathematical activity values Modeling, Inquiry, and Computational Thinking. The success of this transformation depends unequivocally on Teacher Education, which must be structured around the development of the TPACK model (Technological Pedagogical Content Knowledge) and based on reflective and collaborative practice. The new teaching perspective is hybrid and ubiquitous, manifested in Active Methodologies such as the Flipped Classroom, which optimizes face-to-face time for collaborative problem solving, with the teacher acting as a mediator. In addition, teaching should embrace Mathematical Modeling and the use of real data to develop Data Literacy, essential for the 21st-century citizen. In this redefinition, the teacher becomes a Pedagogical Designer and Knowledge Curator, enabling students to use Mathematics critically, ethically, and as a tool for investigation and digital citizenship. DOI: https://doi.org/10.56238/sevened2025.038-041